Business decision making through the ordered weighted average - Baez-Palencia, Diego; Olazabal-Lugo, Maricruz; Romero-Muñoz, Jorge (Unidad Editorial UPTC, 2020)
Abstract The progress of decision making in business is addressed by this document through a theoretical review of research works. To do that, a summary of seminal elements that gave rise to the development of this area is shown, particularly, decision making under uncertainty environments. To this end, studies of different methodological approaches, into the fuzzy type, are included, those and until reaching the initial approach of the ordered weighted average (OWA). The latter being a treatment of flexible and diverse application, it leads to present a description of a set of OWA extensions widely used in the literature. Finally, some applied researches of OWA are detailed, with their results in the business field, which show the relevance this operator has taken, and the range that opens up for the growth of its study. Keywords: Decision making, Uncertainty environment, Fuzzy logic, Ordered weighted average, OWA operator JEL Codes : D81, C02, C65 Received: 28/07/2019. Accepted: 22/04/2020.  Published: 24/05/2020